Kajian Pengelolaan Kawasan Taman Hutan Raya Nipa-Nipa dengan Program Pengelolaan Hutan Berbasis Masyarakat di Sulawesi Tenggara - Mukaddas, Jamal (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2017)
Objectives to be achieved in this study (1). Forms of PHBM program that has been implemented in the Nipa-Nipa Grand Forest Park Region on the utilization block. (2). The success level of PHBM program implementation at the Nipa-Nipa Grand Forest Park Region on the utilization block. (3). Level of conservation area Tahura Nipa-Nipa on the block utilization. Based on the results of studies that (1). Community-Based Forest Management Program that has been implemented in the Nipa-Nipa Grand Forest Park Region on the KTPH utilization block is divided into several areas i.e: biological enrichment area, plantation management area and other areas. The park pattern applied by KTPH is the agroforestry systems. That combine forestry, plantation and Livestock. (2). Implementation of PHBM program in the Nipa-Nipa Grand Forest Park Region on the utilization block has reduced the encroachment. based on the analysis of land use transformation is seen that land use before the PHBM program enter in the Nipa-Nipa Grand Forest Park Region consists of forest, open land, settlements, and shrubs. While the land use after the PHBM program implementation consists of forests, farms, settlements and shrubs. so the PHBM program implementation in the Nipa-Nipa Grand Forest Park Region on the land use that previously was an open land by shifting agriculture turned into a mixed farms managed by farmers' groups of forest conservation. For communities income with an average change of 7.34% this is addressing the changes of people's income level by ≥ 1 so that these changes are positive for all KTPH in the District of Western Kendari. (3). How is the conservation level of the Nipa-Nipa Grand Forest Park Region on the utilization block. The conservation level of Nipa-Nipa Grand Forest Park Region shows that the implications of forest product management in the Grand Forest Park Region to the region conservation is good that the use and the management of forest products have met the minimum requirements of the forest conservation achievement, which is obtained based on the results of each indicator by 75%, This showed a balance in all three conservation principles: the conservation of social function, the conservation of product function, and the conservation of ecological function that is generated by the performance of forest management in the Nipa-Nipa Grand Forest Park Region especially that is implemented by KTPH members. The Management of the Nipa-Nipa Grand Forest Park Region cannot be separated from the role of all relevant stakeholders. For that the management of this Grand Forest Park Region can be made as a pilot unit of a sustainable and consistent forestry development. The results of this study is expected to be a reference to the relevant agencies in order to preserve the Nipa-Nipa Grand Forest Park Region.